Problematika Penerapan Kurikulum Merdeka Pada Mata Pelajaran Aqidah Akhlak di MIS GUPPI 11 Talang Rimbo - Mustakim, Mustakim; Sutarto, Sutarto; Fadila, Fadila (Berkala Ilmiah Pendidikan, 2024)
This study aims to examine the implementation of the Merdeka Belajar Curriculum in the Aqidah Akhlak subject at MIS GUPPI 11 Talang Rimbo and the factors influencing its application. The research method used is descriptive qualitative, with data collection techniques including participatory observation, interviews, and documentation. The results show that the implementation of the Merdeka Belajar Curriculum is well-structured, utilizing various teaching methods and supported by teacher training. Internal factors such as school facilities, infrastructure, and teacher competence play significant roles, while obstacles like limited teaching resources, inadequate training, and resistance to change need to be addressed. The study concludes that strong support from the school, government, and community is essential to improve facilities, provide continuous teacher training, and conduct proper evaluations. Recommendations include enhancing facilities, continuous training, administrative support, and ongoing evaluation to improve the implementation of the Merdeka Belajar Curriculum.